Perancangan Pengalaman Pengguna Aplikasi Pengenalan Batik berbasis Mobile menggunakan Metode Design Thinking - Ivan Lianto; Lutfi Fanani; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Batik is the work of the Indonesian people and is one of the intangible heritages recognized by UNESCO in 2009. However, not many people understand the process behind making batik. The process of learning batik is done manually and is considered less effective for children and adults by visiting the batik gallery. Based on these problems, media is needed to be able to support the introduction of batik using gadgets. The purpose of this study is to propose a design solution that can solve the existing problems and limitations. User experience design is needed so that users get a good experience in terms of being easy to use and learn. The design thinking method is used with the aim of helping to develop user-focused solution designs. The results of the test using usability testing get an effectiveness value of 97.7%, an efficiency value of 0.03 goals/sec, and a satisfaction value using the System Usability Scale (SUS) of 62.5 which is at level D or poor. It can be concluded that the solution design has succeeded in providing a solution even though there are deficiencies in user satisfaction and improvements are needed in accordance with suggestions and input from respondents.